Method of transmission matrix for investigating planar relative motions - Do Sanh; Do Dang Khoa (Vietnam Journal of Mechanics)
In the paper [2] the method of transmission matrix applying for the case of a loop with turning pairs investigated. In the present paper the kinematics of a loop connected by composite joints, i.e. the one of revolute-translational joints are discussed now. By means of proposed method the planar motion of rigid bodies is presented by a point of general view.